Standard surgical versus percutaneous dilatational tracheostomy in intensive care patients - Lukas, Jindrich; Duskova, Jaroslava; Lukas, David; Paska, Jan; Stritesky, Martin; Haas, Tomas (Saudi medical journal, 2007)
OBJECTIVE: The present prospective randomized trial compared surgical tracheostomy (ST) and percutaneous dilatational tracheostomy (PDT) in intensive care unit (ICU) patients in terms of outcomes and complications. METHODS: Between January 2003 and December 2005 tracheostomies were performed on critically ill ICU patients in Medical Faculty Hospital in Prague, with a random allocation of 105 patients for ST and 100 for PDT. RESULTS: The 2 groups did not differ significantly in terms of basic demographic characteristics or length of endotracheal intubation prior to the procedure. Following the procedures, the 2 groups did not differ significantly in terms of the time required for decannulation, decannulated patients or mortalities. Post-mortem examination showed that both groups were similar in terms of placement of the tracheostomy tube. Surgical tracheostomy was found to take longer time to perform than PDT (p<0.001). In terms of early postoperative complications, PDT was associated with a higher rate of postoperative bleeding compared to ST (p=0.0302). CONCLUSION: Percutaneous dilatational tracheostomy is a simpler and faster technique to perform, but is associated with a higher occurrence of early complications, particularly postoperative bleeding.
Keywords: senioři; Intubation, Intratracheal; senioři nad 80 let; tracheostomie; mladiství; výsledek terapie; Middle Aged; mužské pohlaví; Tracheostomy; Prospective Studies; péče o pacienty v kritickém stavu; Adult; intratracheální intubace; Critical Care; Aged, 80 and over; ženské pohlaví; Humans; prospektivní studie; kritický stav; lidé středního věku; dospělí; Female; Aged; Adolescent; Treatment Outcome; Critical Illness; lidé; Male